The Concept of the Manners of Seeking Knowledge According to Imam Al-Ghazali and its Relevance for Contemporary Islamic Education: A Literature Review - Nilam Cahya Munandar; Mutia Lutfi; Toseef Azid (Yayasan Adra Karima Hubbi, 2025)
This study passionately explores the profound and timeless concept of the manners of seeking knowledge championed by the venerable Muslim scholar, Imam Al-Ghazali, and investigates its compelling humanistic relevance for fostering ethical character within contemporary Islamic education. Employing a rigorous qualitative literature review (library research) focused on Al-Ghazali's ethical masterpieces, particularly Ihya' 'Ulum al-Din, the primary objective is to articulate a holistic ethical roadmap for the moral development of both the student and the teacher. Our method involved systematic thematic analysis to uncover Al-Ghazali's core manners principles: sincerity of intention, deep reverence for knowledge, profound humility, patience, and the moral obligation to apply learning for personal and societal betterment. The results demonstrate that Al-Ghazali’s educational philosophy transcends mere intellectual acquisition; it fundamentally seeks human transformation from an unrefined state to a person of wisdom, self-awareness, and ethical integrity. This research offers novelty by synthesizing these classical spiritual-ethical requirements into a deeply relevant, character-centric framework that challenges the current education paradigm's over-emphasis on purely cognitive metrics. The implication is that by consciously integrating this ethical framework, contemporary Islamic education can cultivate responsible, compassionate, and ethically grounded scholars more effectively. While rooted in education, this holistic emphasis on ethical integrity and the pursuit of objective truth is foundational for any scholarly endeavor, critically contributing to the development of science and learning across all disciplines by ensuring that intellectual exploration is always guided by profound human values and responsibility, leading to unbiased research and applications that genuinely serve the greater good of humanity.